Factores de riesgo y de protección de la depresión en los adolescentes de la ciudad de Medellín (2012)
ABSTRACT: Mental disorders have become a key concern in the scientific and epidemiological in recent years. This is because the social consequences that some behaviors of these disorders may involve, reason it is important to inquire about the factors associated with one of the most prevalent mental disorders in the population, depression. The objective is to evaluate the association of risk factors and protective of depression in adolescents in the city of Medellin. Design is a study of Case-Control Analytical which was identified by multivariate analysis the weight of the factors related to depression as the dependent variable. The study population consisted of school pupils from 9 to 19 years living in the city of Medellin, belonging to the public and private schools of the city, was characterized by a mean age of 13.77 with a standard deviation of 2.195 years , 56.7% were female. Statistical analysis was performed with significance level p <0.05, where significant association with family cohesion, OR = 2.35 (CI = 1.63 to 3.41); social scale, OR = 0.657 (CI = 0.453 to 0.953) and Academic Area, OR = 0.534 (CI = 0.408 to 0.699). Environmental factors such as stressful life events, relationship problems with parents, spirituality, affiliation with prosocial peers and antisocial behavior, academic achievement and commitment, have an association against the internalizing disorders, where the depression.